(untitled) (Global Journal of Medical Research, 2015)
Dentinogenesis imperfecta is a developmental disorder affecting the structure of the teeth.Both deciduous and permanent dentition are affected. Deciduous teeth are most severely affected.Early diagnosis and treatment are therefore important to obtain a better prognosis since late intervention makes treatment more complex.